Protection of corneal epithelial stem cells prevents ultraviolet A damage during corneal collagen cross-linking treatment for keratoconus. Issue 2 (28th November 2013) - Moore, Jonathan E; Atkinson, Sarah D; Azar, Dimitri T; Worthington, Jenny; Downes, C Stephen; Courtney, David G; Moore, C B Tara
Abstract : Background/aims: Cross-linking of the cornea is usually carried out at a young age as a treatment to manage ectasia. The corneal limbal region contains delicate long-lived stem cells, which could potentially be deleteriously affected by Ultraviolet A (UV-A) radiation. Damage to these stem cells may not demonstrate as a clinical problem for many years subsequent to cross-linking treatment. UV-A radiation is known to have potential mutagenic effects upon mammalian DNA and can result in cancer. Methods: Cultured corneal epithelial cells and ex vivo corneal tissue were treated with the standard clinical cross-linking protocol for UV-A irradiation. 8-hydroxydeoxyguansoine (8-OHdG) and cyclin-dependent kinase inhibitor genes (CDKN1A and CDKN2A) were assayed as markers of DNA damage using immunohistochemistry, ELISA and quantitative real time PCR. Results: Staining of treated limbal tissue demonstrated the presence of 8-OHdG within p63 positive basal limbal cells. Levels of 8-OHdG and CDKN1A mRNA were found to be significantly increased in cultured corneal epithelial cells and limbal epithelial cells but no increase was demonstrated with the use of a polymethyl methylacrylate protective cover. Conclusions: This study provides evidence that oxidative nuclear DNA damage can occur through cross-linking in layers of corneal epithelial cells at the limbus and that this can be easily prevented by covering the limbus.